Biochar-seeded struvite precipitation for simultaneous nutrient recovery and chemical oxygen demand removal in leachate: From laboratory to pilot scale - Wang, Saier; Sun, Kechun; Xiang, Huiming; Zhao, Zhiqiang; Shi, Ying; Su, Lianghu; Tan, Chaoqun; Zhang, Longjiang (Frontiers in Chemistry, 2022)
Refuse transfer stations (RTSs) leachate treatement call for efficient methods to increase nutrient recovery (NH4+−N and PO43−−P) and chemical oxygen demand (COD) removal. In this study, the effects of various operational factors (seeding dose, pH, initial NH4+-N concentration and reaction time) on biochar seeded struvite precipitation were investigated at laboratory and pilot scales. Mealworm frass biochar (MFB) and corn stover biochar (CSB) were used as seeding materials to compare with traditional seed struvite. The maximum NH4+−N and PO43−−P recover efficiency of MFB seeded process reached 85.4% and 97.5%, higher than non-seeded (78.5% and 88.0%) and CSB seeded (80.5% and 92.0%) processes and close to struvite seeded (84.5% and 95.1%) process. The MFB seeded process also exhibited higher COD removal capacity (46.4%) compared to CSB seeded (35.9%) and struvite seeded (31.2%) processes and increased the average particle size of struivte product from 33.7 to 70.2 μm for better sustained release. XRD, FT-IR, and SEM confirmed the orthorhombic crystal structure with organic matter attached of struvite product. A pilot-scale test was further carried out in a custom-designed stirred tank reactor (20 L). In the pilot-scale test, MFB seeded process still spectacularly recovered 77.9% of NH4+−N and 96.1% of PO43−−P with 42.1% COD removal, which was slightly lower than laboratory test due to insufficient and uniform agitation. On the whole, MFB seeded struvite precipitation are considered to be a promising pretreatment method for rural RTS leachate.